Review of: Alkis Charalampidis,ΜΠΑΡΟΚ: ΑΡΧΙΤΕΚΤΟΝΙΚΗ, ΓΛΥΠΤΙΚΗ, ΖΩΓΡΑΦΙΚΗ [BAROQUE: ARCHITECTURE, SCULPTURE, PEINTURE], Kalliopi Tzimagiorgi (éd.), Thessalonique: University Studio Press, 2017, 221 pages, 290 figures. - Drakopoulou, Eugénie (The Historical Review/La Revue Historique, 2020)
.